Odpowiedź:
Szczegółowe wyjaśnienie:
1.
3x-2y=7
[tex]y=\frac{3}{2} *x - \frac{7}{2} \\proste równoległe:\\y=\frac{3}{2} *x - \frac{7}{2} \\y=\frac{3}{2} *x - \frac{7}{4} \\y=\frac{3}{2} *x - \frac{7}{6} \\y=\frac{3}{2} *x - \frac{7}{7} \\y=\frac{3}{2} *x - \frac{8}{2} \\y=\frac{3}{2} *x - 2\\y=\frac{3}{2} *x - 6\\y=\frac{3}{2} *x - 7\\\\y=\frac{3}{2} *x +55\\y=\frac{3}{2} *x + 77[/tex]
2. 2x-5y=-8
[tex]y = \frac{2}{5} *x + \frac{8}{5}\\Proste prostopadłe:\\ y = -\frac{2}{5} *x + \frac{8}{5}\\ y = -\frac{2}{5} *x + 1\\ y = -\frac{2}{5} *x + 3\\ y = -\frac{2}{5} *x + 6\\ y = -\frac{2}{5} *x + 16\\ y = -\frac{2}{5} *x - 5\\ y = -\frac{2}{5} *x - 55\\ y = -\frac{2}{5} *x - 57\\ y = -\frac{2}{5} *x - 58\\ y = -\frac{2}{5} *x - 5543\\[/tex]